2016
DOI: 10.1021/acs.jnatprod.6b00004
|View full text |Cite
|
Sign up to set email alerts
|

Acredinone C and the Effect of Acredinones on Osteoclastogenic and Osteoblastogenic Activity

Abstract: A new inhibitor, acredinone C (1), of receptor activator of nuclear factor-κB ligand (RANKL)-induced osteoclast differentiation was isolated from the culture broth of the fungus Acremonium sp. (F9A015) along with acredinones A (2) and B (3). The structure of acredinone C (1), which incorporates benzophenone and xanthone moieties, was established by the analyses of combined spectroscopic data including 1D and 2D NMR and MS. All of the acredinones studied efficiently inhibited the RANKL-induced formation of TRAP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…In particular, few anti-osteoporotic compounds with dual action except acredinone have been derived from microorganisms [ 18 ]. In the present study, we identified the novel activity on bone metabolism of austalide K, isolated from cultures of the marine fungus Penicillium rudallense , by demonstrating the simultaneous regulation of the genes related to osteoclast and osteoblast differentiation, as in the acredinone study [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, few anti-osteoporotic compounds with dual action except acredinone have been derived from microorganisms [ 18 ]. In the present study, we identified the novel activity on bone metabolism of austalide K, isolated from cultures of the marine fungus Penicillium rudallense , by demonstrating the simultaneous regulation of the genes related to osteoclast and osteoblast differentiation, as in the acredinone study [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…These are essential genes for the generation of mature multinucleated osteoclasts [ 22 , 23 , 24 ]. In addition, the average percentage reduction of gene expression of the osteoclatogenic major factors by austalide K was more than 80%, compared to around 50% by acredinone [ 14 ]. This means that austalide K strongly inhibited the expression of osteoclast-related genes and might be used as a scaffold for much more effective osteoporotic treatment medicines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, 140 had marked bone-formation potential in the in vivo mouse model, thence, 140 could be a potential lead as an anabolic agent and/or anti-resorptive agent to prohibit and heal bone disorders. 87…”
Section: Biological Activities Of Benzophenonesmentioning
confidence: 99%
“…Table 3 presents not only the pharmacological activity (an IC 50 ), but also the molecular mechanism of action of the following marine natural compounds: Fungus Acremonium sp. (F9A015) polyketide acredinone C (235) [256]; algal terpenoid astaxanthin (207) [257]; sponge Axinyssa sp. bisabolene sesquiterpene (236) [258]; sponge Carteriospongia sp.…”
Section: Marine Compounds With Miscellaneous Mechanisms Of Actionmentioning
confidence: 99%